EKSISTENSIALISME - Dian Ekawati (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Metro, 2015)
School has been considered for long as the center of educational institutions which is able to educate the youth as the nation upcoming generation. The scool success in conducting the qualified educational program mainly depends on the influence of some exsistences like the environment,family and community as the part of either formal of informal educational system. In the modern life, the philosophy of exsistentialism is not only applied in the educational settings, but also in the social life. Acording to the perspective of exsistentialism, the school should give freedom to each individual to do as how they want to since not all individuals have the same interest and orientation and the also have the willingness to be accountable for what they did.